2017
DOI: 10.1093/jac/dkx322
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of pandrug-resistant Acinetobacter baumannii isolates collected from patients with ventilator-associated pneumonia in Greece, Italy and Spain as part of the MagicBullet clinical trial

Abstract: ObjectivesTo investigate the molecular epidemiology, antimicrobial susceptibility and carbapenem resistance determinants of Acinetobacter baumannii isolates from respiratory tract samples of patients diagnosed with ventilator-associated pneumonia (VAP) who were enrolled in the MagicBullet clinical trial.Methods A. baumannii isolates were prospectively cultured from respiratory tract samples from 65 patients from 15 hospitals in Greece, Italy and Spain. Susceptibility testing was performed by broth microdilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 34 publications
9
124
1
3
Order By: Relevance
“…This species is an important agent related to mechanical ventilator-associated pneumonia (VAP), contracted from colonized patients, environmental surfaces, and other unknown sources 8 . In the present study, the respiratory tract was the most important source of CR A. baumannii, which is in accordance with several other countries 9 . The second greatest source of bacteria was catheter tips, which could be indicative of bloodstream infections; or contamination, as previous study reportedy 10 All the CR A. baumannii were positive for bla OXA-51-like and bla OXA-23-like genes, and the detection of bla OXA-51-like confirmed the species identity in all isolates 11 .…”
Section: -Likesupporting
confidence: 93%
“…This species is an important agent related to mechanical ventilator-associated pneumonia (VAP), contracted from colonized patients, environmental surfaces, and other unknown sources 8 . In the present study, the respiratory tract was the most important source of CR A. baumannii, which is in accordance with several other countries 9 . The second greatest source of bacteria was catheter tips, which could be indicative of bloodstream infections; or contamination, as previous study reportedy 10 All the CR A. baumannii were positive for bla OXA-51-like and bla OXA-23-like genes, and the detection of bla OXA-51-like confirmed the species identity in all isolates 11 .…”
Section: -Likesupporting
confidence: 93%
“…Moreover, Mohammadi et al reported similar results among hospitalized patients with burn infection in 2016 in Iran [32]. Therefore, it is not surprising that Chen et al in 2017 in China, Uwingabiye et al in 2017 in Morocco, and Nowak et al in 2017 in Greece, Italy, and Spain reported similar results in their investigations [33], [34], [35]. The percentage of bla OXA-24-like genes, which encode acquired carbapenemases, was 93.6% in the present study, followed by bla OXA-40-like with 48.9%.…”
Section: Discussionmentioning
confidence: 75%
“…In accordance with the previous studies, eravacycline MIC values ranged from 0,5-4 mg/L for OXA-23 and OXA-51 producing CRAB strains in our study. Considering the prevalence of OXA-type carbapenemase activity in CRAB strains, eravacycline has been evaluated as a good treatment option (20–22). However, some type of carbapenemase activity, increased expression of the efflux pumps and the presence of tigecycline resistance are associated with increasing MIC values for eravacycline (1, 3).…”
Section: Discussionmentioning
confidence: 99%